Functional reconstruction of total upper eyelid defects with a composite radial forearm‐palmaris longus tenocutaneous free flap: A report of two cases. Issue 6 (21st January 2019) - Iwanaga, Hiroyuki; Nuri, Takashi; Okada, Masashi; Ueda, Koichi
Abstract : This report presents reconstruction of wide‐ and full‐thickness upper eyelid defects with a composite radial forearm–splitting palmaris longus tendon flap, which maintains eyelid opening and closing functions and supporting tissue in a Meibomian gland carcinoma in the right upper eyelid (case 1) and Merkel cell carcinoma in the right upper eyelid (case 2). After tumor resection with excisional margins, the defects involved the muscle, tarsal, and mucosa, with defect sizes of 60 × 40 mm and 85 × 40 mm, respectively. A radial forearm flap with the palmaris longus tendon was transferred. The tendon was split into two strips: the upper strip was fixed to the frontal muscles for the opening function and the lower strip to the medial palpebral ligament and orbicularis oculi muscle to maintain the closing function. Flap vessels were anastomosed to the superficial temporal artery and vein through the subdermal tunnel. Postoperative courses were uneventful. At the 5‐year (case 1) and 4‐year (case 2) follow‐up periods, there were no tumor recurrence and keratalgia, and the eyelid opening and closing functions were maintained. This approach may contribute to achievement of not only the opening function but also the closing function of the reconstructed eyelid.